2021
DOI: 10.19080/ijesnr.2021.28.556233
|View full text |Cite
|
Sign up to set email alerts
|

Removal of PFAS from Water by Plants

Abstract: Perfluorinated alkylated substances (PFAS) has been produced the last five decades as wetting agents, stain-resistant treatments, lubricants, impregnation sprays and corrosion inhibitors. Among the most common and toxic are perfluoro octane sulfonate (PFOS) and perfluorooctanoic acid (PFOA), which are found among others in blood, soil and water. They need to be removed from water and the aim was to investigate the removal capacity by a terrestrial plant, Salix viminalis, two emergent plants, Carex rostrata and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Previous studies have estimated the PFAS removal of plants. However, these studies were often performed briefly (≥14 days) or in hydroponics experimental setups (Zhang et al 2019;Sharma et al 2020;Greger et al 2021). A study of various willow cultivars also obtained removal efficiency between 2-30% in leaves of willow grown in hydroponics experiments following eight days of PFAS exposure (Sharma et al 2020).…”
Section: Removal Efficiency and Mass Balance (Papers III And Iv)mentioning
confidence: 99%
“…Previous studies have estimated the PFAS removal of plants. However, these studies were often performed briefly (≥14 days) or in hydroponics experimental setups (Zhang et al 2019;Sharma et al 2020;Greger et al 2021). A study of various willow cultivars also obtained removal efficiency between 2-30% in leaves of willow grown in hydroponics experiments following eight days of PFAS exposure (Sharma et al 2020).…”
Section: Removal Efficiency and Mass Balance (Papers III And Iv)mentioning
confidence: 99%
“…In hydroponic experiments, aquatic plants displayed potential to remove PFASs from the aquatic environment [25]. Greger et al treated leakage water from a landfill with plants, and the results showed that the removal capacity of aquatic plants (42.1%) was higher than that of terrestrial plants (7.7%) [26,27]. The aquatic plant removal rate of PFOA and PFOS was more than 82% after treatment for 15 days in the study by Chen et al [28].…”
Section: Introductionmentioning
confidence: 99%